Leiomyosarcoma of mandible-a rare case report with review of literature - Rastogi, Nupur; Gautam, Kaushal; Rohatgi, Sunidhi; Khandelwal, Anushree; Rajawat, Priya (International Journal of Research in Medical Sciences, 2024)
Sarcomas are rare group of malignant mesenchymal tumors, about 1% of all malignancies in adults, leiomyosarcoma constitute 3-10% of all sarcomas in the head and neck region, of them only 0.64% are in oral and maxillofacial region, hence qualifying to be an extremely rare malignancy due to rarity of smooth muscle in that area. Till date approximately 65 cases from 1950-2011 were identified and 20 cases from 2012 till 2024 (as per google search) have been described. We present a case of 51-year-old female who presented with polypoidal growth in right lower alveolus without any lymph node involvement. On histomorphological features and immunohistochemistry, diagnosis of leiomyosarcoma was confirmed.